The Effect of Cigarette Smoke Exposure on the Incidence of Acute Respiratory Infections in Toddlers - Dina Supriyati; Jafar Arifin; Dyah Ambarwati; Prihatini Dini Novitasari (Indonesian Journal of Global Health Research, 2026)
ARI remains one of the leading causes of death among infants, and the incidence of ARI is still quite high in the working area of the Simpang Timbangan Community Health Center. This study aims to determine the relationship between exposure to cigarette smoke and the incidence of ARI among infants in the working area of the Simpang Timbangan Community Health Center. This study used a cross-sectional approach involving 90 households with infants (infants, mothers, and family members who smoke) selected through purposive sampling to assess the relationship between the presence or absence of family members who smoke, CO levels, smoking locations, and the number of cigarettes smoked per day. Statistical analyses used included the Mann-Whitney test, Fisher's exact test, and chi-square test. Results: There were 35.6% of toddlers who experienced ARI. Furthermore, toddlers who lived with family members who smoked were significantly 1.64 times more at risk of experiencing ARI, and among toddlers who lived with smokers, they were 4.55 times more at risk of experiencing ARI if the smokers smoked inside or outside the house. The number of cigarettes smoked per day was also significantly associated with ARI, but CO levels were not significantly associated with ARI. Thus, the presence or absence of smokers, the location of smoking, and the number of cigarettes smoked per day were significantly associated with ARI, although CO levels were not significantly associated.